“SO STONED”: Common Sense Approach of the Dizzy Patient - Wuyts, Floris L.; Van Rompaey, Vincent; Maes, Leen K. (Frontiers in Surgery, 2016)
The history taking of a dizzy patient is of utmost importance in order to differentiate the possible etiologies of vertigo. The key factors that allow a first approximation of diagnosis identification are based on the time profile, symptom profile, and trigger profile of the disease. Here, the proposed mnemonic “SO STONED” comprises eight different dimensions that characterize the vertigo-related complaints of the patient and guide the clinician in his or her decision scheme. All the letters “SO STONED” have a specific meaning: Symptoms, Often (Frequency), Since, Trigger, Otology, Neurology, Evolution, and Duration. Since the most common vestibular diseases have different fingerprints when all dimensions are considered, this tool can facilitate the identification of the appropriate vestibular diagnosis.